2009
DOI: 10.1007/s00421-009-1290-4
|View full text |Cite
|
Sign up to set email alerts
|

Critical environmental limits for exercising heat-acclimated lean and obese boys

Abstract: Environmental limits for uncompensable heat stress, above which an imbalance between heat gain and heat loss forces body core temperature upward (i.e., the upper limits of the prescriptive zone), are unknown for children. To determine these limits, 7 lean and 7 obese 9- to 12-year-old heat-acclimated boys performed four randomized trials each on separate days to determine the critical water vapor pressure (Pcrit) forcing an upward inflection of body core temperature at several ambient temperatures. Subjects wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 32 publications
(42 reference statements)
2
29
0
3
Order By: Relevance
“…[40][41][42][43][44][45][46][47][48] Although two studies showed similar heart rate and core temperature responses to cycling exercise in the heat between obese and lean individuals, 47,48 participants in these studies were performing non-weight-bearing activity at a relative intensity (percentage maximal oxygen uptake [%VO 2max ]) where obese individuals had a significantly lower fitness level, and therefore a lower work output. Conversely, when obese and lean participants performed weight-bearing exercise at a controlled rate (i.e., treadmill walking at a specific speed) in a hot and/or humid environment, obese individuals had elevated heart rates, 40,41,43,46 lower evaporative heat loss, 43,46 greater core temperature increases, 40,46 and more body heat storage 40,46 compared with age-matched, lean controls.…”
Section: Obesitymentioning
confidence: 98%
See 1 more Smart Citation
“…[40][41][42][43][44][45][46][47][48] Although two studies showed similar heart rate and core temperature responses to cycling exercise in the heat between obese and lean individuals, 47,48 participants in these studies were performing non-weight-bearing activity at a relative intensity (percentage maximal oxygen uptake [%VO 2max ]) where obese individuals had a significantly lower fitness level, and therefore a lower work output. Conversely, when obese and lean participants performed weight-bearing exercise at a controlled rate (i.e., treadmill walking at a specific speed) in a hot and/or humid environment, obese individuals had elevated heart rates, 40,41,43,46 lower evaporative heat loss, 43,46 greater core temperature increases, 40,46 and more body heat storage 40,46 compared with age-matched, lean controls.…”
Section: Obesitymentioning
confidence: 98%
“…44 In a study attempting to determine critical environmental limits for exercise in heat-acclimated boys, obese participants had a lower maximal evaporative capacity and failed to maintain heat balance at a lower temperature and/or relative humidity than their lean counterparts. 45 It is difficult to assess the additional impairment in local heat loss responses conferred by the presence of type 2 diabetes in obese individuals. Most studies reviewed in the present article matched their participants with diabetes with age-and sex-matched controls, but not for body mass index or body composition.…”
Section: Obesitymentioning
confidence: 99%
“…In particular, low-income counties that tend to have a low climate amenity, might thus be doubly disadvantaged if there are no community facilities that provide opportunities for indoor physical activities [12]. Further, overweight and obesity, more prevalent in low socioeconomic populations, also increase vulnerability to climate change and higher temperatures [13,14].…”
Section: Climate Change Versus Health: the Mediterranean Basinmentioning
confidence: 99%
“…Climate warming was also suggested to increase overweight and obesity [12], and was found to put a higher burden on overweight individuals [13,14]. In the last 4-5 decades, economic opportunities and availability of indoor climate control have enabled a greater percentage of the US population to reside in places with less desirable climate.…”
Section: Climate Change Versus Health: the Mediterranean Basinmentioning
confidence: 99%
“…This is especially true for illnesses that involve gastrointestinal distress (eg, vomiting, diarrhea) and/or fever. Notable chronic clinical conditions and medications that contribute to decreased exerciseheat tolerance and increased exertional heat-illness risk include diabetes insipidus, 18 type 2 diabetes mellitus, 19 obesity, 20,21 juvenile hyperthyroidism (Graves disease), 22 cystic fibrosis, 23 and anticholinergic drugs or certain other medications that affect hydration or thermoregulation (eg, a dopamine-reuptake inhibitor to treat attention-deficit/hyperactivity disorder or enhance performance 24 or diuretics). Any other chronic or acute medical condition 25 or injury 26 that adversely affects water-electrolyte balance, thermoregulation, and exerciseheat tolerance warrants particular concern as well.…”
Section: Introductionmentioning
confidence: 99%